Controversial elements about socio-environmental changes and landscape dynamics in dogon country (Mali) - (:unkn) unknown (My University, 2019)
This article, using the analysis of changes in the Dogon country (Mali), examines the catastrophic descriptions of the evolution dynamics of West African landscapes and environment. Studies on those dynamics, which are frequently characterised as desertification, relies on inappropriate bases. Our aim is not to deny the material reality of the degradation and its consequences on the communities but to throw light on the transformation processes with a different perspective and thus help to reinvent the definitions of the so-called ecosystem restoration and protection programs which, through their simplistic practices, help to increase the vulnerable nature of the socioecological systems that they wish to sustain.
Keywords: African Research